Left ventricular function in double inlet left ventricle before the Fontan operation: comparison with tricuspid atresia. Issue 4 (October 1988) - Redington, A N; Knight, B; Oldershaw, P J; Shinebourne, E A; Rigby, M L
Abstract : Fourteen patients with double inlet left ventricle and nine patients with tricuspid atresia had biplane left ventricular angiography with simultaneous measurement of left ventricular pressure by micromanometer. Age distribution, haemodynamic function, and previous palliative operation were similar in the two groups. Left ventricular volumes were calculated frame by frame throughout the cardiac cycle by Simpson's rule. The end diastolic volume index was similar in the two groups, but the ejection fraction was significantly lower in tricuspid atresia. Left ventricular peak filling and emptying rates were also lower in tricuspid atresia, although heart rates in the two groups were similar. End diastolic shape index was significantly higher in patients with tricuspid atresia, indicating a more globular shape, and changed less during systole, suggesting differences in the mechanism of ejection between the two groups. Analysis of pressure-volume loops showed normal phase relations between pressure and volume, but systolic stroke work was reduced in tricuspid atresia and correlated with stroke volume and shape change. Left ventricular function was impaired in patients with tricuspid atresia when compared with those with double inlet left ventricle and this finding may reflect structural differences caused by the absence of one atrioventricular connection.